Phenotypic diversity of bamboo Schizostachyum lima (Blanco) Merr. population grown in several critical habitats on Lombok Island, Indonesia - EVY ARYANTI; ESTRI LARAS ARUMINGTYAS; RODLIYATI AZRIANINGSIH; ENDANG ARISOESILANINGSIH (Society for Indonesian Biodiversity, 2023)
Abstract. Aryanti E, Arumingtyas EL, Azrianingsih R, Arisoesilaningsih E. 2023. Phenotypic diversity of bamboo Schizostachyum lima (Blanco) Merr. population grown in several critical habitats on Lombok Island, Indonesia. Biodiversitas 24: 2788-2796. This study aims to analyze the phenotypic diversity among populations of Schizostachyum lima (Blanco) Merr. grown in several critical habitats on Lombok Island. Sampling was conducted to record clump growth and habitat properties of 38 sites grouped based on the clump density using PAST 4.11 and ArcGIS 10.8.2 software. Sampling was conducted to record clump growth and habitat properties of 38 sites grouped based on the clump density using PAST 4.11 and ArcGIS 10.8.2 software. The results showed that habitat 1 was the most critical land and had the lowest fertility, but it provided a qualified bamboo as a raw material for the artisanal straw industry. The results showed that habitat 1 was the most critical land and had the lowest fertility, but it provided a qualified bamboo as a raw material for the artisanal straw industry. Bamboo density reached 46 culms per clump and had the smallest culms diameter of 13 mm. Bamboo density reached 46 culms per clump and had the smallest culms diameter of 13 mm. The soil comprised 90% sand, with SOC 0.9 g.kg-1, total N 0.08 g.kg-1, and CEC 8.3 me.100 g-1. The soil comprised 90% sand, with SOC 0.9 g.kg-1, total N 0.08 g.kg-1, and CEC 8.3 me.100 g-1. Meanwhile, habitat 6 and habitat 7 were lesser critical, consisted of 66% of sand, showed the best soil fertility, and mean SOC 4.98 g.kg-1, total N 0.30 g.kg-1, CEC 27.23 me.100 g-1, density 151 culms, and biggest culms diameter 33 mm. Meanwhile, habitat 6 and habitat 7 were lesser critical, consisted of 66% of sand, showed the best soil fertility, and mean SOC 4.98 g.kg-1, total N 0.30 g.kg-1, CEC 27.23 me.100 g-1, density 151 culms per clump, and biggest culms diameter 33 mm. The other habitats varied in soil quality and bamboo growth properties. It was revealed that the high culms density, diameter, height, and internodal length were significantly increased in the high soil CEC, SOC, and total N. Furthermore, the SOC and total N content significantly correlated with the wall thickness.